(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2013)
أجري التهجين نصف التبادلي بين ست سلالات مرباة داخلياً من الذرة السكرية خلال صيف 2010 في مركز البحوث العلمية الزراعية باللاذقية, محطة بحوث صنوبر جبلة, وزرعت السلالات الأبوية وهجن الجيل الأول في موسم 2011 بهدف دراسة ظاهرة قوة الهجين والقدرة على التوافق لكل من صفة ارتفاع النبات, ارتفاع العرنوس, قطر العرنوس, عدد الصفوف بالعرنوس وإنتاجية النبات الفردي من العرانيس الخضراء. أبدت غالبية الهجن لصفة إنتاجية النبات الفردي قوة هجين موجبة وعالية المعنوية قياساً بمنوسط الأبوين والأب الأفضل, وكان أفضلها 198.70%,176.81% للهجين(L4xL6) و196.94%, 168.56% للهجين (L3xL4)وذلك قياساً لمتوسط الأبوين والأب الأفضل على التتالي. أشارت النسبة ما بين تباين القدرة العامة والخاصة على التوافق σ2GCA/σ2SCA التي كانت أقل من الواحد, إلى أهمية نسبية للفعل الوراثي اللاإضافي مقارنة بالفعل الوراثي الإضافي في وراثة جميع الصفات عدا صفتي ارتفاع النبات وارتفاع العرنوس, وأظهرت السلالتين L3(17.061),L4 (12.011) قدرة عامة جيدة على التوافق لصفة الغلة, كما أظهرت عدة هجن قدرة خاصة جيدة على التوافق لصفة إنتاجية النبات الفردي كان أفضلها الهجين L3xL5 (50.173). A half diallel set of crosses among six inbred lines of sweet corn was evaluated to study heterosis and combining ability among plant height, ear height, ear diameter, number of rows per ear and ear yield per plant. The study was carried out at the agricultural research center in, GCSAR, Lattakia, Snoubar Jableh, during the 2010, 2011 seasons. Result showed that almost all crosses expressed a significant positive heterosis effect for ear yield per plant relative to mid parents and better parents; whereas, the highest positive significant percentage of heterosis for ear yield per plant were expressed by the crosses (L4xL6) which gave (198.70%, 176.81%) and (L4xL6) which gave (196.94%, 168.56%), over mid parents and better parents, respectively. The ratio (σ2GCA/σ2SCA) which was less than (1) showed that the non-additive gene action was more important than the additive gene action in all traits except plant height and ear height. The inbred lines L3 (17.061) and L4 (12.011) seemed to be the best general combiners for ear yield. Also, based on SCA effects, many of single crosses were identified as superior for ear yield, and the best hybrid was L3xL5(50.173).